Impaired embryo development potential associated with thyroid autoimmunity in euthyroid infertile women with diminished ovarian reserve - Zhang, Yongjie; Zhang, Yuchao; Su, Zhuolun; Ren, Bingnan; Yu, Shuang; Li, Wenjing; Xu, Ninghua; Lou, Hua (Frontiers in Endocrinology, 2024)
The aim of this study was to evaluate the associations of thyroid autoimmunity (TAI) with the number of oocytes retrieved (NOR), fertilization rate (FR), and embryo quality (EQ) in euthyroid women with infertility and diminished ovarian reserve (DOR).Methods: This retrospective cohort study involved 1,172 euthyroid women aged 20-40 years with infertility and DOR who underwent an oocyte retrieval cycle. TAI was diagnosed in the presence of serum thyroperoxidase antibody (TPOAb) concentrations higher than 34IU/ml and/or serum thyroglobulin antibody (TgAb) concentrations exceeding 115.0 IU/ml. Among these women, 147 patients with TAI were classified as the TAI-positive group, while 1025 patients without TAI were classified as the TAI-negative group. Using generalized linear models (GLMs) adjusted for confounding factors, we evaluated the associations of TAI, and the serum TPOAb and TgAb concentrations and NOR, FR, and EQ in this study subjects. The TPOAb and TGAb values were subjected to log10 transformation to reduce skewness. Logistic regression models were used to estimate the effects of TPOAb and TgAb concentrations on the probabilities of achieving a high NOR (≥7) and high FR (>60%).Results: For the whole study population, women with TAI had a significantly lower NOR and poorer EQ than women without TAI (P < 0.001 for both). Interestingly, in the TSH ≤ 2.5 subgroup, the TAIpositive group also had a significantly lower NOR and poorer EQ than the TAI-negative group (P < 0.001 for both). Furthermore, negative associations were observed between log10(TPOAb) concentrations and NOR and number of high-quality embryos and available embryos (P < 0.05 for all). The log10(TgAb) concentrations were inversely associated with NOR and number of high-quality embryos (P < 0.05 for all). In the regression analysis, the log10(TPOAb) concentrations had lower probabilities of achieving a high NOR (adjusted odds ratio [aOR]: 0.56 [95% confidence interval, CI 0.37, 0.85]; P = 0.007).Conclusions: TAI and higher TPOAb and TgAb concentrations were shown to be associated with reductions in the NOR and EQ in the study population. Our findings provide further evidence to support systematic screening and treatment for TAI in euthyroid women with infertility and DOR.